Human services contemporary issues and trends (Princeton, N.J. Recording for the Blind & Dyslexic, 2005)
Through articles by ... scholars in the field, this text introduces, defines, and analyzes the movement behind human services theory and application. The text leads the reader on a path from the basics and origins of human services, to information on working with clients such as children, families, and special populations, to familiarizing readers with the laws and ethics of human services. -Back cover.
Human services, origins, development, and basics: Basic concepts and definitions of human services / P.F. Cimmino; Historical roots of human services / J. Diambra -- Human service professionals, skills, values, and standards: Human services, necessary skills and values / L.A. Long and M. Doyle; Helping services for groups / B. Somerville -- Human service work with families and children: Domestic violence, battered women, and dimensions of the problem / M. Munoz-Kantha; Youth and human services / W. de Oliveira and C.R. Edginton -- Human service clients, special populations: Human services for homeless people / L.A. Long; Helping services for older adults / K.J. Niccum -- Changing the system(s) in human services: Policy, politics, and human services / H.L. McPheeters; Community organizing as human service / L. Stuart -- Law, ethics, and professional issues: Law, ethics, and the human service worker / N. Blair -- Emerging issues and trends: Trends and challenges of cultural diversity / R.D. Petrie; Technology and human services / S. Rosenzweig -- Appendixes: Mid-term interview, observer rating form; Mid-term interview, self-evaluation paper.
Originally published: Boston : Pearson/Allyn and Bacon, c2004. 3rd ed.
Includes bibliographical references.
Keywords: Human services personnel; Human services